FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA DOKTER SPESIALIS RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG PASCA IMPLEMENTASI JAMINAN KESEHATAN NASIONAL - Amalia Choirun Nafi'ah; Criswardani Suryawati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
ABSTRAK: The National Health Insurance (JKN) characterized the operation of the Badan Penyelenggara Jaminan Sosial Kesehatan on 1st January 2014. The medical specialist plays an important role related to health care in hospital. Preliminary study of the specialist, obtained complaints less comfortably with INACBG's (Indonesian Case Base Groups) and medical services. The purpose of this study was to analyze factors related to job satisfaction specialist in Islamic Hospital Sultan Agung (RSISA) post-JKN. This type of research using quantitative and qualitative methods with cross sectional design. Most tetap respondents (56.5%) perceive less satisfied and as much as 69.2% of mitra respondents perceive satisfied. Most tetap respondents (56.5%) perceive poor medical services, 52.2% good working conditions, 69.6% administrative discretion good organization, poor leadership 52.2%, 69.6% good interpersonal relationships, and 52.2% less good promotion opportunities. Most mitra respondents (53.8%) perceive a good medical services, 61.5% good working conditions, 61.5% administrative discretion poor organization, 53.8% good leadership, 61.5% good interpersonal relationships, and 61.5% good chance of promotion.There relationship between the perception of medical services (p = 0.007), there is a correlation between the perception of working conditions (p = 0.003), there was no correlation between the perception of the organization's policy administration (p = 0.194), there the relationship between the perception of leadership (p = 0.019), there was no correlation between the perception of interpersonal relationships (p = 0.345) and there is a correlation between the perception of promotion opportunities (p = 0.047) and job satisfaction specialist. Several factors related to job satisfaction RSISA is a specialist in medical services, working conditions, leadership, and promotion opportunities. Management can improve job satisfaction evaluation specialists to conduct an ongoing job satisfaction, optimizing gathering, seeking disclosure of the calculation of medical services, and to seek equal opportunities training.